Perlakuan Terhadap Tawanan Perang Yang Tidak Manusiawi - Salakory, Eddi Emi Christin; Hanafi, Irma Halima; Riry, Welly Angela (Faculty of Law Universitas Pattimura, 2025)
Prisoner of war (POW) is a member of the armed forces captured during wartime. Prisoner of war should be treated with high protection and respect, free from violence, threats, and torture. The US soldiers' inhumane treatment of prisoners in Abu Ghraib prison, Iraq, exemplifies a serious human rights violation. Recently, former Ukrainian prisoner of war reported being tortured in southwestern Russia, including beatings and electric shocks. This thesis employs Normative Law research, focusing on positive legal norms through a dogmatic approach to understand their relationships with legal principles and institutions. The study highlights that Geneva Convention III of 1949 obligates states to arrest, prosecute, and punish violators of prisoners of war rights. The US adhered to these obligations by prosecuting six military personnel involved in Abu Ghraib torture but is not required to compensate for its officials' or agents' involvement. Conversely, Russia has not addressed its treatment of Ukrainian prisoner of war, underscoring the need for adherence to International Humanitarian Law and International Conventions to safeguard prisoner of war rights.